PROFIL ETIKA DAN KOMPETENSI ALUMNI PROGRAM STUDI PENDIDIKAN BIOLOGI - Hutasoit, Leonard R.; Kismiati, Dyah Aniza; Ratnaningsih, Anna; Wahyuningsih, Tri; Nurhasanah, Nurhasanah; Nurdin, Gusti (Inteligensi : Jurnal Ilmu Pendidikan, 2023)
Research related to alumni in a study program is often carried out to determine the quality of a university. It is no exception in distance universities such as Universitas Terbuka (UT). This study aims to determine how the ethical profile and competency profile in the field of biology education in alumni of the Biology Education study program, Faculty of Teacher Training and Education, Universitas Terbuka. This survey study was conducted using the alumni user population of UT Biology Education students with a research sample of 35 people. There are five indicators to measure the ethical profile of alumni and five indicators related to competency profile. The five ethical indicators include respect, not looking down on others, respecting the opinions of others, behaving politely, and helping others. Alumni competency indicators consist of providing opportunities for students to master the material, carry out learning according to the curriculum, analyze student learning outcomes, play an active role in various activities, and prepare learning materials. The alumni users include the principals and vice principals of the schools where alumni teach. The sample is acquired based on the random sampling techniques. Data was obtained through interviews and questionnaires given to alumni users.  Next, the data is analyzed descriptively. The result, informed us about the average ethical profile of biology education alumni was 89.57 while the average profile of competence or expertise in the field of science was 84.71. Thus, the ethical profile and competence of alumni of Biology Education at the Open University are high